Hydroxychloroquine usage in US patients, their experiences of tolerability and adherence, and implications for treatment: survey results from 3127 patients with SLE conducted by the Lupus Foundation of America - Daniel J Wallace; Leslie Hanrahan; Karin Tse; Rupert Davies (Lupus Science and Medicine)
The majority of patients with SLE in the USA have been prescribed hydroxychloroquine (HCQ). Given more recent guidelines, the availability of only one strength (200 mg tablets) may limit the flexibility and ability to accurately dose patients with lupus. The Lupus Foundation of America undertook a survey to assess the current landscape of HCQ tolerability and adherence.